The four feathers [videorecording (DVD)] - Kapur, Shekhar, 1945-; Ledger, Heath, 1979-2008; Bentley, Wes, 1978-; Hudson, Kate, 1979-; Hounsou, Djimon, 1964-; Cameron, Allan; Mason, A. E. W. (Alfred Edward Woodley), 1865-1948 (Paramount Pictures, 2003)
After an admired soldier leaves his regiment in disgrace, he sets out on a sweeping adventure to regain his honor, recapture his love and save the life of his best friend.